1985
DOI: 10.1007/bf02917464
|View full text |Cite
|
Sign up to set email alerts
|

Iron, zinc, and copper content in the tissues of the rat during pregnancy

Abstract: The levels of iron, zinc, and copper in the tissues of the pregnant rat, on d 12, 19, and 21 after impregnation have been determined and compared with controls. Iron levels decreased considerably in late pregnancy as a result of increased fetal requirements, thus diminishing iron stores in rat tissues, but maintaining the circulating plasma levels. Copper levels increased slightly at midpregnancy, but returned to control levels at the end of gestation. Zinc stores also increased slightly during early pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
15
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
5
15
0
Order By: Relevance
“…Zinc plasma levels were high in the fetus and in the neonate, in agreement with pre vious results [16,20]. It is known that there is a very active transfer in the placenta at term for this element [3,4,6,7], which leads to higher concentrations in the fetal circulation than in the maternal one [16,20], These high circulating concentrations would secure the supply of this essential element to all the tis sues that are in great need of zinc during a phase of accelerated growth.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Zinc plasma levels were high in the fetus and in the neonate, in agreement with pre vious results [16,20]. It is known that there is a very active transfer in the placenta at term for this element [3,4,6,7], which leads to higher concentrations in the fetal circulation than in the maternal one [16,20], These high circulating concentrations would secure the supply of this essential element to all the tis sues that are in great need of zinc during a phase of accelerated growth.…”
Section: Discussionsupporting
confidence: 66%
“…This increase is generated in the maternal stores and is reflected in low lev els of circulating copper, which would be mostly retained in the liver [5,16]. Cerulo plasmin levels are also low during this period, as a consequence of the lack of ability of the fetal and neonate livers to synthesize it at maximum [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies of trace mineral deposition in the fetus have been reported for the rat (Mas et al 1985) and sheep (Langlands et al 1982;Grace et al 1986). Except for a report on maternal-fetal Zn utilization in 24 heifers (Hansard et al 1968 (Mills 1985).…”
mentioning
confidence: 99%
“…Despite zinc being a metal in rather short supply during pregnancy [1], and the needs of the fetuses being important [27], the maternal organ ism was able -on day 17 -to maintain its reserves through increased intestinal absorption when receiv ing adequate supplies of this metal through the diet [28], The zinc status of fetuses and placentae was comparatively better in the case of tumour-bearing pregnant mice, as they contained more zinc, and the host had also more zinc in proportion to its weight than the only pregnant mice; the tumour, however, contained a somewhat lower proportion of zinc. On the other hand, the tumour-bearing mice had much less overall zinc compared with controls, with the losses of the host tissues being parallel to the loss of tissue mass.…”
Section: Discussionmentioning
confidence: 99%